Concept and Significance of Criminalistics Classification of Crimes Related to Proxy Battle (Law and Safety, 2019)
The author of the article has analyzed the state of scientific development of criminalistics classification of crimes related to proxy battle in order to prove the need for further research taking into account amendments in the current legislation, as well as current conditions.Special attention has been paid to the fact that the current criminal law in Ukraine does not handle the categories of “raidership” or “crimes related to proxy battle”; besides, the Criminal Code of Ukraine does not contain the separate Section that would include the list of criminal offenses in in this area, and the norms that provide criminal liability for certain actions accompanied by proxy battle, are dispersed between different Sections of the Special Part of the Code. The legislator while constructing their corpus delicti (perhaps, with the exception of the disposition of the Art. 206² of the Criminal Code of Ukraine) did not use wording indicating the commission of proxy battle. This has resulted in the lack of the unity among scholars – national and international experts specialized in criminalistics, criminology, criminal and other branches of law within the stated issue, as well as among representatives of economic science, although they offered certain approaches to the classification of raidership manifestations.Taking into account the analyzed scientific points of view, the author has offered the classification of crimes related to proxy battle in accordance with criminal criteria, according to the purpose of committing the crime, as well as according to certain elements of criminalistics characteristic of the researched category of crimes, such as: crime’s modus operandi (the most important), situation, tools, means, crime scene, its consequences, direct object of criminal assault, conditions of its protection against assault, offender’s personality and the way of his life before and after the commission of the crime (including the presence or absence of criminal experience), the victim’s personality and characterizing him information, the ways of hiding the traces of the crime and the perpetrator.It has been concluded that suggested grounds for criminalistics classification of crimes related to proxy battle are not exhaustive, and this necessitates further research in this area in order of further improvement of investigation method of the specified category of crimes.
Keywords: criminalistics classification; crimes related to proxy battle; raidership